INTEGRATED AQUACULTURE ADAPTATION TO CLIMATE CHANGE: CASE OF SHRIMP – RICE ROTATION FARMING SYSTEM IN KIEN GIANG PROVINCE - Minh Thanh, Nguyen; Thi Thu Ha, Tran; Tien Chuong, Ngo (Journal of Forestry Science and Technology, 2019)
The paper aims to improve sustainability of the integrated aquaculture adaptation to climate change by analysing the case of shrimp – rice rotation farming system in An Bien district, Kien Giang province. The survey was conducted with 100 households and group discussions with different stakeholders in the district. The results show that shrimp farming in the model bring more benefit than the rice monoculture system. However, the financial efficiency of shrimp farming is affected by the way of farming that the households applied (using of nursing pond and fingerling testing). In the context of climate change, the system intermediates between rice cultivation and shrimp farming which helps farmers gradually adapt in order to stabilize and improve their income. The model also brings social contributions such as creating seasonal job, stimulating the development of logistic activities. In terms of environmental sustainability, controlling use of chemicals and antibiotics, and ability to expand the system to other districts are the main benefits. For sustainable development of the model, a number of suggestions have been made for improving land use planning and investment; strengthening quality management and inspection of shrimp farming; and improving production organization & management and extension services.